Creating Dynamic Learning Communities in Synchronous Online Courses: One Approach from the Center for the Integration of Research, Teaching and Learning (CIRTL) - McDaniels, Melissa; Pfund, Christine; Barnicle, Kitch (Online Learning, 2016)
The ability to convert face-to-face curricula into rigorous and equally rich online experiences is a topic of much investigation. In this paper, we report on the conversion of a face-to-face research mentor training curriculum into a synchronous, online course. Graduate students and postdoc participants from the Center for the Integration of Research, Teaching and Learning (CIRTL) reported high satisfaction with the online training and increased confidence in their mentoring. Both quantitative and qualitative data indicate that the synchronous environment was successful in creating a strong sense of community among the participants. Specific pedagogical approaches for cultivating learning communities online as well as implications for scaling up such efforts are discussed.